Lectura, escritura, matemáticas y habilidades digitales en la escuela. Hacia la necesidad de alfabetizaciones académicas continuas - González de la Torre, Yolanda; Jiménez Mora, José (Universidad de Costa Rica, 2021)
Authors' teaching background ranging high school to postgraduate education allow to notice students’ lack of basic knowledge. Therefore, it is argued the need to recover that basic knowledge at each educational level to facilitate the acquisition and construction of knowledge, through processes that can be explained in the literature from the concept academic literacy, focused in four aspects: reading, writing, mathematics and use of information and communication technologies. The main argument holds that when dealing with basic knowledge that students would be expected to have consolidated at each level, the fact that they are not demonstrated gives rise to the need to define and, if necessary, help students learn such knowledge. It is concluded that this could improve their performance in tasks of knowledge acquisition and construction according to what is demanded of them at the level they are in, as well as becoming familiar with the requirements of the disciplinary fields in which they are trained, in the case of who are undergraduate and graduate.